2010
DOI: 10.1016/j.rdc.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cell Interactions in Rheumatoid Arthritis Synovium

Abstract: Synopsis Understanding the pathogenesis of joint inflammation and destruction in rheumatoid arthritis involves dissection of the cellular and molecular interactions that occur in synovial tissue. Development of effective targeted therapies has been based on progress in achieving such insights. Safer and more specific approaches to treatment could flow from discovery of cell-cell interaction pathways that are relatively specific for inflammation of the joint, and less important in defense against systemic infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 50 publications
0
62
0
4
Order By: Relevance
“…V arious immune effector cell types, including CD4 + T cells, have been implicated in the pathogenesis of rheumatoid arthritis (RA) (1). Indeed, the synovial tissue of RA patients is infiltrated with IFN-g-and IL-17-producing CD4 + T cells, resulting in synovial inflammation and joint cartilage destruction (2).…”
mentioning
confidence: 99%
“…V arious immune effector cell types, including CD4 + T cells, have been implicated in the pathogenesis of rheumatoid arthritis (RA) (1). Indeed, the synovial tissue of RA patients is infiltrated with IFN-g-and IL-17-producing CD4 + T cells, resulting in synovial inflammation and joint cartilage destruction (2).…”
mentioning
confidence: 99%
“…The majority of these studies showed that methotrexate (MTX) and leflunomide were able to induce apoptosis in vitro in a variety 1 c-kit tyrosine kinase is a mast/stem cell growth factor receptor also known as CD117 [131] 2 ZAP-70, ζ-chain-associated protein-70 and a member of the tyrosine kinase family that is normally expressed by T-cells and natural killer cells [132] 3 SIRT1 is silent mating type information regulation 2 homolog (sirtuin-1) and a deacetylating enzyme [133] 4 PAR-2, Protease-activated receptor-2 and a subfamily member related to G-protein coupled receptors that may be activated by cleavage through their extracellular domain [134] 5 NF-AT5, Nuclear factor of activated T-cells 5 belonging to the NFAT family of transcription factors [135] 6 Human umbilical vascular endothelial cells 7 Mcl-1, Induced myeloid leukemia cell differentiation protein [136] 8 Epigallocatechin-3-gallate 9 MDC, myeloid-derived cells; PDC, plasmacytoid-derived cells 10 Apaf-1, Apoptotic protease activating factor-1 11 An inhibitor of geranylgeranyl transferase [137] 12 An inhibitor of RhoA kinase [138] 1 REL1096 is the p65 (Rel A) subunit of NF-κB 2 GADD45β is the growth arrest and DNA-damage-inducible45β protein [148] 3 Putative consensus sites for the binding of miR-124a and miR-146a to the 3'-untranslated regions of cyclin-dependent kinase-2 (CDK-2) and MCP-1, respectively 4 Putative consensus site for the binding of miR-146a to the 3' untranslated region of Fas-associated factor-1 of cells pertinent to RA pathology as well as cells involved in generalized inflammation, including, T-cells, neutrophils, mast cells and macrophages. By contrast, although NSAIDS were proposed as potential apoptosis inducers [166], the NSAID, celecoxib, failed to induce apoptosis in RAFLS in vitro [171].…”
Section: Apoptotic Responses To Anti-ra Therapiesmentioning
confidence: 99%
“…Most prominent among these pro-inflammatory cytokines are tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1) as well as IL-6, IL-7, IL-8, IL-12/IL-23, IL-15, IL-17, IL-18, IL-32, interferon-γ and growth factors, including, fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor (VEGF), the latter produced principally by T-and B-lymphocytes and macrophages. The combination of these cytokines and growth factors cause a dysregulation of synoviocyte proliferation that lead to the development of synovial tissue hyperplasia [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…활막 조직의 내막층(intimal lining layer)에는 대식세포 들이 분포하며, 내막하층(subintimal layer)에는 대식세포 (macrophage)와 섬유아세포 유사 활막세포(fibroblast like synoviocyte: FLS)가 분포하고 있다 [5]. 두 세포군은 형태학 적 및 생물학적 기능에 분명한 차이를 보인다.…”
Section: 서 론unclassified
“…대식 세포는 관절강 내의 불필요한 물질들을 제거하는 역할을 수행할 뿐 아니라 항원을 제시함으로서 면역반응에 관여한다. FLS는 류마티스 관절염환자의 활막내 만성 염증을 유지하고 병의 증상을 악화시키는 역할을 한다 [5,9]. 즉, 류마티스 관절염 발 병과정에서 IL-1은 FLS를 자극하고, IL-6, IL-8과 같은 염증성 사이토카인의 분비를 촉진하며 부착인자의 발현을 증가시켜 염증반응을 유도한다 [10].…”
Section: 서 론unclassified